The lost art of Scripture: rescuing the sacred texts - Armstrong, Karen (The Bodley Head, 2019)
Cosmos and society -- Israel: remembering in order to belong -- India: sound and silence -- China: rites first, spirits second -- Mythos -- New story; new self -- Empathy -- Unknowing -- Canon -- Midrash -- Embodiment -- Recitation and Intentio -- Ineffability -- Logos -- Sola Scriptura -- Sola Ratio -- Post-Scripture.